Sinking in sports ; Wanted barrio doctors ; Racing across American [Videorecording] - Lazaro, Cheche (The Probe Team, 1993)
President Ramos clean-up on Philippine Sports Commission through Eric Buhain's confession at his frustrating experiences with the government's sports agency. Health Secretary Juan Flavier offers a nice salary for those willing to serve in areas that have been doctorless for ten years. A debate o the kind of medical education that we give and the kind of doctors we get. The bicycle racer Maui Reynante being invited to join the World's longest bicycle race.